Business opportunities during pandemic COVID-19 for alumni / Arith Syakir Bunsu ... [et al.] - Bunsu, Arith Syakir; Daniel, Nur Zafika; Ramsa, Rizwanshah; Siti Nur Syazwanie; Empang Wan, Veronica (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The Covid-19 pandemic has caused a profound and damaging impact on the global economy, including the rise in unemployment. One of the significant trends that emerged from the pandemic is the decline of graduate recruitment volumes due to the closure of several business activities among employers. As a result, more graduates are likely difficult to enter the labour market and not able to earn a living.